Introduction to the International Symposium on Lipid Science and Health and research progress in lipid science and health - Fang Wei (KeAi Communications Co., Ltd., 2021)
The International Symposium on Lipid Science and Health (ISLSH), which was organized annually by Oil Crops Research Institute of Chinese Academy of Agricultural Sciences (OCRI-CAAS) since 2016, has gained a strong reputation and attracted hundreds of delegates from around the world for discussion of lipid research trends and advances every year, to promote research and academic exchanges in the fields of lipid science and health. The 5th International Symposium on lipid Science and Health was successfully held in Wuhan, China, from October 23rd to 25th, 2020, to celebrate the 60th anniversary of OCRI-CAAS. The two-day symposium gathered well-known experts specialized in lipid science to share the current state of lipid research with emphasis on aspects covering: (1) lipid profiling and characterization, (2) lipid preparation and modification, (3) lipid improvement and regulation, and (4) lipid nutrition and health. The symposium was conducted by a combination of on-site and network meeting. More than 250 distinguished delegates from academia and industry participated in the on-site multidisciplinary meeting, and thousands of scholars attended the virtual event. This paper is as a record of the symposium proceedings and a brief summary of the advances and trends in 4 aspects of lipid science and health.